EFFECTS OF NITROGEN FERTILIZER RATE AND PLANT DENSITY ON STRAW, SEED YIELD, AND QUALITY OF THREE LINUM USITATISSIMUM L. CULTIVARS - Gaber Y. M. Allam; Salah A. H. Hammam (American Journal Of Agriculture And Horticulture Innovations, 2023)
The objective of this study was to investigate the effects of nitrogen fertilizer rate and plant density on straw, seed yield, and quality of three Linum usitatissimum L. cultivars. The study was conducted in a randomized complete block design with three replicates. The cultivars used were Linola 947, Linola 989, and CDC Bethune. Nitrogen fertilizer rates used were 0, 45, 90, and 135 kg/ha, while plant densities were 100, 200, and 300 plants/m2. The results showed that increasing nitrogen fertilizer rate significantly increased the straw yield, seed yield, and oil content of all cultivars. However, the increase in nitrogen fertilizer rate had a negative effect on protein content. Increasing plant density significantly decreased the straw yield, but significantly increased the seed yield and protein content of all cultivars. Oil content was not significantly affected by plant density. Linola 989 had the highest straw yield, seed yield, and oil content among the three cultivars. CDC Bethune had the highest protein content.